Toward a More Robust New Materialist Politics: How the Practice of Criminal Animal Trials Can Inform Contemporary Politics - Reyna, Zachary Low (Stasis, 2020)
Prior to the twentieth century, animals were routinely put on trial in human courtrooms. This curious practice has received little academic attention. In this article, I examine the phenomenon of animal trials as an “old” New Materialism. Both part and parcel of the Western legal systems that gave rise to modern law and somehow excessive or extravagant to modern law, the practice of putting animals on trial provides insight into how occidental law and politics has traditionally grappled with the question of the nonhuman, and also the potentialities and shortcomings of recent attempts to include the nonhuman in modern law and politics. The goal of this article is not to resuscitate these archaic practices, but to explore a path not taken by modern law, and so open a route for both deepening our appreciation of the historical possibilities of a New Materialist politics and pushing it further.